2005
DOI: 10.1038/sj.npp.1300930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the NMDA Antagonist Ketamine on Task-Switching Performance: Evidence for Specific Impairments of Executive Control

Abstract: In humans, the effects of subanesthetic doses of ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, substantially impair executive control functions. Here, we consider whether ketamine exposure can provide an animal model for the effects of ketamine on executive control. Two monkeys (Macaca mulatta) performed a cued task-switching paradigm. We studied their behavior before and after a range of ketamine doses. We found that ketamine slowed overall performance and decreased overall accuracy, strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 46 publications
5
36
0
Order By: Relevance
“…Although we attempted to control for this with the addition of a polydrug control group, it was apparent that the ecstasy user group smoked significantly more cannabis and consumed significantly more cocaine than this group. Furthermore there were 9 participants in the ecstasy user group who reported using ketamine in the last 30 days, compared to none in the polydrug group, this is potentially problematic for the interpretation of the current results given the association between ketamine use and executive function deficits in humans (for a review see Morgan & Curran, 2006), and specifically that switching has been shown to be impaired in animals with ketamine exposure (Stoet & Snyder, 2006).…”
Section: Limitationsmentioning
confidence: 89%
“…Although we attempted to control for this with the addition of a polydrug control group, it was apparent that the ecstasy user group smoked significantly more cannabis and consumed significantly more cocaine than this group. Furthermore there were 9 participants in the ecstasy user group who reported using ketamine in the last 30 days, compared to none in the polydrug group, this is potentially problematic for the interpretation of the current results given the association between ketamine use and executive function deficits in humans (for a review see Morgan & Curran, 2006), and specifically that switching has been shown to be impaired in animals with ketamine exposure (Stoet & Snyder, 2006).…”
Section: Limitationsmentioning
confidence: 89%
“…Between the control block and the treatment block, animals randomly received an intramuscular injection of ketamine (Ketaset; 0.25, 0.5, 0.75, or 1 mg/kg diluted to 0.3 ml with saline), 0.3 ml of saline solution (0.9% sodium chloride) as a vehicle control, or no injection (to control for waning motivation as the animals became more satiated). Although ketamine is a dissociative anesthetic, doses Յ1.0 mg/kg have been reported not to cause debilitating effects on behavior while reliably affecting saccade latency and metrics (Shiigi and Casey, 1999;Condy et al, 2005;Stoet and Snyder, 2006;Brunamonti et al, 2007). Data were collected from three sessions per treatment per monkey, with the exception of one additional session collected from monkey G with a ketamine dose of 1.0 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced cognitive function is considered to be the most debilitating aspect of schizophrenia as the severity of these symptoms directly relates to the patient's quality of life and current pharmaceutical interventions provide minimal improvement (Elvevåg and Goldberg, 2000;Goldman-Rakic et al, 2004;Goeree et al, 2005;van Os and Kapur, 2009). Nonhuman primates also show similar cognitive deficits following systemic subanesthetic doses of ketamine as patients with schizophrenia in a number of behavioral tasks (Condy et al, 2005;Stoet and Snyder, 2006). An example is the antisaccade paradigm, which requires the inhibition of a prepotent prosaccade toward a flashed peripheral stimulus in favor of the generation of a saccade away from the stimulus toward the opposite direction (Everling and Fischer, 1998;Munoz and Everling, 2004).…”
Section: Introductionmentioning
confidence: 95%